2010
DOI: 10.1088/1748-6041/5/5/054114
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic cell response on fluoridated hydroxyapatite coatings: the effect of magnesium incorporation

Abstract: Magnesium (Mg) ions were incorporated into fluoridated hydroxyapatite (HA) coating by the sol-gel dip-coating method. Mg in the coating was measured by x-ray photoelectron spectroscopy (XPS). The changes of calcium and magnesium concentrations were recorded to monitor the dissolution behavior of the coatings. In vitro cell responses were evaluated using MG63 cells in terms of cell morphology, proliferation and differentiation. The substitution of Mg and F ions into the HA crystal structure was confirmed by XPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 23 publications
5
37
1
Order By: Relevance
“…In this case, as calcium phosphate particles, they also participated to the precipitation of apatite-like crystals onto the scaffold surface from the bulk. However, the presence of the bioactive coating did not cover the bioactive signal of MgCHA particles, which was mediated by the release of Mg, Ca and P ions to cells as reported in previous study 29 …”
Section: Discussionmentioning
confidence: 61%
“…In this case, as calcium phosphate particles, they also participated to the precipitation of apatite-like crystals onto the scaffold surface from the bulk. However, the presence of the bioactive coating did not cover the bioactive signal of MgCHA particles, which was mediated by the release of Mg, Ca and P ions to cells as reported in previous study 29 …”
Section: Discussionmentioning
confidence: 61%
“…Firstly, surface treatment with inorganic ions induces a significant roughness modification which is responsible, in turn, of an increased cell adhesion and of a reduced osteoblasts cytotoxicity, as demonstrated in our previous paper 9) . Furthermore, it can be argued that magnesium and calcium addition on test surface plays a pivotal role in promoting and enhancing cell differentiation thus improving bone-implant contact, as supported by the scientific literature 21,22,24) . However the reasons of this outcome still remain unknown and need to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, as the scientific literature widely demonstrated some inorganic ions, such as magnesium and calcium, are able to stimulate hard tissue regeneration by promoting osteoblasts proliferation and differentiation 21,22) . It was hypothesized that the addition of calcium and magnesium inorganic ions (CaMg) to the implant surface could increase the levels of PGE2 and the expression of BMP2 and RUNX2, generally considered osteoblastic differentiation markers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated similar results where cells on Mg containing surfaces showed higher proliferation and differentiation compared to Mg-free specimens. 30,38,39 Furthermore, Mg ions are considered to be beneficial for bone cell attachment. Zreiqat et al 23 reported that cells grown on Mg-modified alumina exhibited a significantly increased adhesion since binding of integrins to specific ligands depends on the presence of divalent cations.…”
Section: Discussionmentioning
confidence: 99%